Evaluation and management of symptomatic duodenal diverticula: a single-center retrospective analysis of 647 patients - Ren, Jiaqiang; Ding, Jiachun; Su, Tong; Wu, Shuai; Chen, Fan; Li, Jie; Wang, Zheng; Han, Liang; Wu, Zheng (Frontiers in Surgery, 2023)
To explore the clinical characteristics of patients with symptomatic duodenal diverticula and to generalize how to make appropriate treatment choices for this group of patients.From January 2010 to September 2020, a total of 647 patients with duodenal diverticula (DD) were included in this study. 345 of them with relevant symptoms were divided into the symptomatic group and the other 302 patients were in the asymptomatic group.Results Among all patients, most DD were located in the periampullary area, <1cm in size， and single in number. The distribution of DD localized in the 2nd portion/periampullary (P=0.002/P<0.001) and with a 1cm size cut-off value (P=0.003) was significantly different between the symptomatic and asymptomatic groups. Multivariate Logistics analysis further suggests that diverticular size (<1cm, 1-3cm) and combined biliary comorbidities (bile duct stones and gallstones, primary bile duct stones, cholangitis without bile duct stones) may be factors influencing the choice of treatment modality. Of all patients undergoing surgical treatment, a total of 7 cases developed various postoperative complications, and no one died.Patients with DD ≥1 cm or located in the periampullary were more likely to be symptomatic. The specific size of the DD and the combination of specific biliary comorbidities may have an impact on the choice of treatment modality.